The experience of patients with fear-avoidance belief hospitalised for low back pain – a qualitative study. Issue 4 (13th February 2016) - Stisen, Dorte Barfred; Tegner, Heidi; Bendix, Tom; Esbensen, Bente Appel
Abstract: Purpose : Severe pain, anxiety, depression, and fear-avoidance belief (FAB) are widespread among patients hospitalised for acute low back pain (LBP). Research shows that these psychological factors impact negatively on rehabilitation. This study aimed to investigate and develop an understanding of pain in patients with fear avoidance belief hospitalised for LBP. Method : Semi-structured interviews were conducted with nine patients selected by an FAB questionnaire: averaged FAB – physical activity score was 21 and FAB – work score was 30. All participants were recruited from a rheumatology ward. Analyses were based on the content analysis. Results : The analysis revealed two main categories: (1) back history until the pain became dominant, demonstrating the importance of the LBP histories before admission to hospital. (2) Being in a universe of pain verified, the severe pain expressed through metaphors and a need to be involved in the rehabilitation. During interviews, the participants did not indicate high FAB behaviour. Conclusions : Despite high scores, the FAB questionnaire might not be sufficient to detect FAB in patients hospitalised for acute LBP. It is important to include the deeper meaning of metaphors and the personal story behind the expression of pain as a way of understanding each individual with LBP. Implications for Rehabilitation: FAB questionnaire is not sufficient either to detect fear avoidance in LBP patients hospitalised with acute conditions or to catch the complexities of individual pain experiences. It seems essential for health care professionals (HCP) to involve the patient in their treatment and development of a rehabilitation plan based on their individual histories and concerns about the future. The metaphors expressed are a way for HCPs to gain insight into the psychological aspect of pain for the individual patient.